Body and Belief: Exploration in African Ritology. The Magic of Body Language - Uzukwu, Elochukwu (Jaarboek voor liturgieonderzoek, 2008)
'Body and Belief’ evoke the cosmo-biological. The rhythm of time and seasons impacts on humans, and humans in turn respond with adequate gestures and rituals. Human development, from birth to death, invites potent transition ritu-als that refuse to go away despite modernity-postmodernity. My presentation assumes the cosmo-biological while adopting a wider anthropo-cosmological horizon.